The Net Effect of an Alcohol Tax Increase on Death Rates in Middle Age - Cook, Philip J; Ostermann, Jan; Sloan, Frank A (American Economic Review, 2005)
The Net Effect of an Alcohol Tax Increase on Death Rates in Middle Age by Philip J. Cook, Jan Ostermann and Frank A. Sloan. Published in volume 95, issue 2, pages 278-281 of American Economic Review, May 2005